Factors Influencing Implementation of Peace Education Programme in Primary Schools: A Case of Tharaka North District - Mbogo, Esther Wawira; Ndiritu, Dr. Anne (International Journal of Entrepreneurship and Project Management, 2016)
Purpose: The purpose of the study was to establish the factors influencing implementation of peace education programme in primary schools located in Tharaka North District. The researcher was guided by the following specific objectives: to establish whether school leadership influence implementation of peace education programme in primary schools in Tharaka North District, to find out whether school resources influence implementation of peace education programme in primary schools in Tharaka North District, to determine whether school culture influence implementation of peace education programme in primary schools in Tharaka North District. Methodology: The study used a descriptive research design. A population of 317 schools was identified. A sample of 32 schools was taken. 96 respondents from the 32 schools were identified preferably consisting of three categories, a headteacher, an upper primary teacher and a lower primary teacher. A questionnaire was the data collection instrument. The analysis consisted of descriptive and inferential statistics. Specifically, descriptive statistics included means while the inferential statistics included correlation analysis. Results: The study findings indicated that school leadership, culture, and resources influence peace education programme implementation. Correlations results indicated that there was a positive and significant relationship between peace education programme implementation and school leadership, culture and resources. Unique contribution to theory, practice and policy: The study recommends school management to emphasize on peace education programme implementation in all primary schools. The study also recommends that the schools to emphasize on good leadership and management skills so as to ensure smooth implementation process. The study recommends further that the school management should set aside enough resources for the implementation of programme as organization resources positively affect organizational efficiency through its impact on internal capabilities and finally the study recommends that the school management should learn the culture of different parts of the country so as to make the teachers, parents and children welcome and adopt the programme if it values its culture